Vascular Inflammation and Cardiovascular Burden in Metastatic Breast Cancer Female Patients Receiving Hormonal Treatment and CDK 4/6 Inhibitors or Everolimus - Papageorgiou, Christos; Zagouri, Flora; Tampakis, Konstantinos; Georgakopoulou, Rebecca; Manios, Efstathios; Kafouris, Pavlos; Benetos, Georgios; Koutagiar, Iosif; Anagnostopoulos, Constantinos; Dimopoulos, Meletios A.; Toutouzas, Konstantinos (Frontiers in Cardiovascular Medicine, 2021)
Background: Chemotherapy for breast cancer treatment can promote vascular dysfunction and lead to high cardiovascular risk. Purpose: To investigate the cardiovascular burden and vascular inflammation in metastatic breast cancer patients receiving CDK 4/6 inhibitors or everolimus in addition to standard hormonal treatment. Methods: 22 consecutive female patients with metastatic breast cancer were enrolled. Relative wall thickness (RWT) and left ventricle mass (LVM) measurements by transthoracic echocardiography were obtained followed by 24-hour ambulatory blood pressure monitoring, and 18F-fluorodeoxyglucose positron-emission tomography/computed tomography imaging. Uptake of the radiotracer in the aortic wall was estimated as tissue-to-background ratio (TBR). Each patient was assessed for the aforementioned parameters before the initiation and after 6 months of treatment. Results: At follow up, patients assigned to CDK 4/6 treatment demonstrated increased 24-hour systolic blood pressure (SBP) (p=0.004), daytime SBP (p=0.004) and night time SBP (p=0.012) (Group effect). The 24-hour mean arterial pressure measurements were also higher in CDK 4/6 population, in comparison to everolimus that displayed firm values. (Group effect- p=0.035, Interaction effect-p=0.023). Additionally, 24 hour diastolic blood pressure recordings in CDK 4/6 therapy were higher opposed to everolimus that remained consistent (Interaction effect- p=0.010). In CDK 4/6 group, TBR aorta also increased significantly, whereas TBR values in everolimus remained stable. (Interaction effect-p=0.049). Both regimens displayed statistically significant damaging effect to RWT and LVM. Conclusion: CDK 4/6 inhibitors and hormonal treatment can lead to increased vascular inflammation, and higher blood pressure compared to the combination of everolimus and hormonal treatment. Moreover, both treatments promoted left ventricle remodeling.